The compensatory mechanism and clinical significance of hydrocephalus after cranioplasty - Qiu, Xiansheng; Wang, Dong; Chen, Li; Huang, Guanlin; Zhou, Xiaoping; Chen, Qiang; Wang, Zhanxiang (Frontiers in Neurology, 2023)
Objective: Induced hydrocephalus after decompressive craniectomy (DC) requires cranioplasty (CP) and ventriculoperitoneal shunting (VPS) to protect the cranial surface and prevent hydrocephalus. This study evaluated the safety and efficacy of different surgical sequences of CP and VPS after DC and identified risk factors for the need for permanent VPS. Methods: Between January 2017 and December 2021, 192 patients underwent staged CP and/or VPS after DC. Cumulative medical records and radiological data were analyzed using univariate analysis to determine the efficacy of patient preference for CP and/or VPS and to document information on freedom from VPS after CP and to identify risk factors for the need for permanent VPS. Results: Preferential CP or preferential VPS surgery was chosen in 86 (22.2%) and 106 (77.8%) cases, respectively. There were no significant differences in surgical complications or surgical outcomes between the two groups in terms of the Barthel Index, FMAS, Mrs, GCS, and Evans' index scores, but 29 (33.7%) patients who chose priority CP were eventually spared from VPS. Univariate analysis showed that the primary etiology, area of skull defect, distance from the edge of the bone flap to the midline, and lumbar puncture pressure were predictors of the need for permanent VPS after CP. Conclusion: This study provides detailed information on the efficacy and complications of different sequences of preferential CP or VPS after DC surgery. We found that priority CP reduced the incidence of VPS surgery without affecting surgical outcomes and complications.